Model assessment of individual tumor control rate and adverse effects in comparing locally advanced cervical cancer treatment using intracavitary with and without interstitial brachytherapy - Kuo, Hsiang-Chi; Mehta, Keyur J; Yaparpalvi, Ravindra; Shankar, Viswanathan; Bodner, William; Garg, Madhur; Rivera, Amanda; Tomé, Wolfgang A.; Kalnicki, Shalom (Journal of Contemporary Brachytherapy, 2016)
Purpose : This study assessed the modeled probability of tumor control and organ at risk toxicities in locally advanced cervical cancer in patients treated by external beam radiation plus brachytherapy using intracavitary combined with interstitial brachytherapy (IC/IS) vs. intracavitary brachytherapy (IC) alone. Material and methods: Twenty cervical cancer patients with a mean HR-CTV volume of 47.4 cm3 and a mean width of 54 mm were planned with both IC/IS and IC brachytherapy alone. A probit model was utilized to model 3-year (3-yr) local control rate (LC), 3-yr cancer specific survival rate (CSS), and the adverse effect (AE) of the organ at risk by using a modeled data set from multiple institutions. Modeling results were used to estimate the LC, CSS, and AE of the treatments in this study. Results: Using the IC/IS technique, an EQD2 increase of 12.3 Gy to D90 (from 76.1 Gy to 88.3 Gy) of HR-CTV is expected to increase 3-yr LC and 3-yr CSS by 12.5%, and 11.0%, respectively. Comparing IC/IS to IC alone, the expected G2+ AE were 7.7% vs. 7.9% for the bladder, and 5.9% vs. 6.8% for the rectum. Conclusions : The IC/IS technique improved dose coverage to the HR-CTV without significantly increasing dose to 2 cm3 of the organ at risk (OAR) surrounding it. With different regimens of EBRT combined with BT, IC/IS can be used to increase the probability of LC and CSS, or decrease the risk of AE.